ChemInform Abstract: An Efficient Synthetic Protocol for Quinoxalinones, Benzoxazinones, and Benzothiazinones from 2‐Oxo‐2‐aryl‐acetyl Bromide Precursors. Issue 7 (18th February 2014) - Nagaraj, Muthupandi; Sathiyamoorthy, Sithuraj; Boominathan, Muthusamy; Muthusubramanian, Shanmugam; Bhuvanesh, Nattamai
Abstract Reaction of 2‐oxo‐2‐arylacetyl bromides (II), obtained by SeO2 oxidation of α‐bromoketones, with phenylenediamines, o‐aminophenol and o‐aminothiophenol provides a facile and efficient access to quinoxalinones, benzoxazinones and benzothiazinones, respectively.